Laik Fungsi Pemanfaatan Bagian-Bagian Jalan Soekarno Hatta Kota Malang - Ratnaningsih, Dwi; Wahiddin; Pudjowati, Utami Retno (Journal of Civil Engineering, 2025)
The challenges of traffic congestion mean that the condition of road infrastructure, including sidewalks, pedestrian crossings and other supporting facilities, needs serious attention. Damages or lack of maintenance can be detrimental to the comfort of road users and increase the risk of accidents. Therefore, it is necessary to conduct an in-depth study to evaluate and ensure the technical serviceability of various parts of Soekarno Hatta Road. Primary data required include: Road Geometrics, separators, median pavement, pedestrian facilities, land use and access properties. Secondary data required include: population of Malang City, location map, road status. Analysis of the serviceability of the Technical Function Utilisation Study of Parts of Soekarno Hatta Road - Malang City refers to the Regulation of the Minister of Public Works No. 11/PRT/M/2010. The results of the analysis obtained factors that affect the technical serviceability of the utilisation of road parts include: Rumaja, Rumija, Ruwasja and Sidewalks. categorised as Conditional Functioning Condition.